Study on covert administration of medications practices among persons with severe mental illness: A cross-sectional study. (February 2023) - Hegde, Prakyath R; Gowda, Guru S; Vajawat, Bhavika; Basavaraju, Vinay; Moirangthem, Sydney; Naveen Kumar, Channaveerachari; Bada Math, Suresh
Background: Covert administration of medication (CoAdM) by caregivers to persons with severe mental illness (SMI) is a commonly observed medication delivery practice in India. Aims: This study aims to examine different medication delivery practices adopted by caregivers to provide care to SMI at times of medication refusal. Method: This study was conducted at the outpatient department between April 2019 and November 2019. A semi-structured questionnaire was used to interview the caregivers of persons with SMI to assess medication delivery practices. Results: A total of 300 caregivers were interviewed. CoAdM was practiced in 96 (32.0%) persons with SMI at least once during their lifetime, and other strategies used were pleading ( n = 105, 35.0%), lying ( n = 10, 3.3%), and threatening ( n = 154, 51.4%). Logistic regression showed that male gender (OR 4.75; CI 1.37–16.46), absent insight (OR 10.0; CI 2.01–47.56), and poor adherence to medication (OR 4.75; CI 1.31–16.92) were significantly associated with CoAdM in the last 1 year. Caregivers perceived significant improvement in self-care ( Z = −4.37, p < .01), interpersonal ( Z = −7.61, p < .01), work ( Z = −5.9, p < .01), family functioning ( Z = −7.82, p < .01) difficult behavior ( Z = −8.27, p < .01), and dependency ( Z = −6.34, p < .01) in persons with SMI with use of CoAdM. Conclusions: CoAdM was given to one in three persons with SMI at some point in their lives. Male gender, absent insight and poor adherence were predictive of CoAdM in the last 1 year. Caregiver perceived improvements in self-care, work, interpersonal, family functioning, problem behaviors, and dependency after CoAdM. Policies need to be evolved to serve all stakeholders while keeping these practices in mind.